2017
DOI: 10.12788/jhm.2695
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bedside Interdisciplinary Rounds on Length of Stay and Complications

Abstract: BACKGROUND: Communication among team members within hospitals is typically fragmented. Bedside interdisciplinary rounds (IDR) have the potential to improve communication and outcomes through enhanced structure and patient engagement. OBJECTIVE: To decrease length of stay (LOS) and complications through the transformation of daily IDR to a bedside model. DESIGN: Controlled trial. SETTING: 2 geographic areas of a medical unit using a clinical microsystem structure. PATIENTS: 2005 hospitalizations over a 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…Likewise, a non-bundled intervention by Gausvik et al 56 resulted in an improvement in 30-day readmission for patients discharged to a skilled nursing facility (SNF) (11.68% vs 14.7%, p<0.05), decreased LOS for patients discharged to an SNF (5.24 days vs 7.26 days, p<0.001) and decreased LOS for patients discharged to home (3.73 days vs 4.21 days, p=0.001). However, bundled interventions involving BR by Dunn et al 39 and Saint et al 48 did not result in a statistically significant difference in LOS when compared with control units.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Likewise, a non-bundled intervention by Gausvik et al 56 resulted in an improvement in 30-day readmission for patients discharged to a skilled nursing facility (SNF) (11.68% vs 14.7%, p<0.05), decreased LOS for patients discharged to an SNF (5.24 days vs 7.26 days, p<0.001) and decreased LOS for patients discharged to home (3.73 days vs 4.21 days, p=0.001). However, bundled interventions involving BR by Dunn et al 39 and Saint et al 48 did not result in a statistically significant difference in LOS when compared with control units.…”
Section: Resultsmentioning
confidence: 83%
“…Likewise, a bundled BR intervention by Stein et al 28 led to a decrease in unadjusted mortality (1.1% vs 2.3%, p=0.004). However, Dunn et al 39 found no statistically significant effect of BR on composite outcomes of clinical deterioration or hospital-acquired conditions (7.7% vs 9.3%, p=0.46). Other results in this domain included no statistically significant effect of BR on adherence with outpatient follow-up appointments (9.5% vs 14.3%, p=0.63) 26…”
Section: Resultsmentioning
confidence: 97%
“…Bedside IDR focuses on the daily plan and patient safety by utilizing a scripted format. 3 Our multifaceted intervention included prompting the hospitalist physician during bedside IDR, education of the clinicians, and regular data review for the hospitalists and unit staff.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2015 study, Gausvik et al found higher agreement on team communication, perceptions of safety and job satisfaction amongst practitioners using IDR compared to a physician‐centric model (). Similarly, nurses and physicians noted improved efficiency and patient safety with bedside IDR in a 2017 study (Dunn et al, ). Consistent with these results, (Henkin et al, ) noted improved agreement in physicians and nurses’ perceptions of interdisciplinary collaboration after the introduction of IDR.…”
Section: Introductionmentioning
confidence: 94%